Influência da condição financeira governamental sobre os gastos com investimento público nos maiores municípios brasileiros - Souza, Deborah Chaussê de Freitas (2020)
This research aimed to analyze the influence of government's financial condition (CFG) on public investment in the largest Brazilian cities. Based on the Cuts Management Theory, we assumed that public investment is reduced when cities present unfavorable financial condition. The sample comprised data collected from 2010 to 2018 in 94 Brazilian cities. The data were analyzed using the regression model with panel data. The dependent variable consisted of investment spending and the independent variable comprised the CFG, which had a proxy for measurement, the Payment Capacity model proposed by the Secretaria do Tesouro Nacional (STN) (BRASIL, 2017). Two econometric models were proposed with differences in the explanatory variables of interest: the first considered the final classification obtained in the calculation of the CFG; and the second split the CFG into the three indicators, according to the STN model: I. Debt; II. Liquidity; and III. Current Savings. The results from the first model indicated a trend of higher spending on public investments by cities with better CFGs when compared to cities that showed signs of deterioration in this index. However, there was no statistical significance in this relation. The results associated with the split model of the CFG suggested that the Debt and Liquidity indicators are not significantly related to the degree of public investment. The Current Savings index, in turn, has a significant relation with the amount earmarked for investments, and suggests that the level of current savings positively influences public investment spending. This work contributes to the literature, indicating that Current Savings can be used as a determining factor for municipal investments. Lastly, this research contributed to the municipal public management serving as an advice to managers about the importance of knowing and preserving the municipal government's financial condition to maintain the investment capacity in public infrastructure, develop long-term management and promote sustained economic growth